Physicochemical, Antimicrobial, Lethality and In Vitro Antioxidant Profiles of Johnu Tisane: A Coffee (Coffea Arabica) Leaf Decoction Formula - Egbuonu, Anthony Cemaluk Chinedum; Alaebo, Prince Ogochukwu; Onuoha, Udumma Nsofor; Njoku, Chinomso Juliet; Obike, Chiemeziem Adanma; Nlemadim, Susan Ogechi; Chukwu, Blessing Ifeoma; Iwejuo, Sopuruchi Mary-Augusta; Amaechi, Onyedikachi Glory; Obiefuna, Victor Ifechukwu; Onuoha, Bessing Nmesomachi; Okoli, DivineTreasure Nzubechukwu; Nwokeoma, Precious Chinonso; Eze, Chukwubuikem (Biology, Medicine, & Natural Product Chemistry, 2024)
Coffee leaves-based tea has relevance in ethno-medications due to its rich phyto-constituents-related diverse pharmacologic activities. Jonhu tisane, a typical Coffea arabica leaf decoction has no supporting scientific basis amidst reported location, processing and specie-related variations. This investigated physicochemical, antimicrobial, lethality and in-vitro antioxidant profiles of Johnu tisane by acceptable methods. Results recorded moisture (92.26 %), ash (0.65 %), unsaponified matter (1.46 mg/100 g), free fatty acid (0.56 mgKOH/g), acid value (1.12 mgKOH/g), potential hydrogen (6.85), lethal concentration (1000 ppm) and concentration-dependent antimicrobial activity. Anti-oxidation results revealed total antioxidant capacity, ferric reducing antioxidant power, nitric oxide, hydrogen peroxide and 2, 2-diphynyl-1-picrylhydrazyl scavenging activities increased concentration-dependently compared to standard. Thus, Johnu tisane demonstrated low minerals and keeping quality; requisite physicochemical mix for consumption and bioactivity; high safety margin; antimicrobial potency; and requisite anti-oxidation capacity for in-vivo antioxidant role. These provided scientific support for its ethno-medicinal uses. They underscored the need to elucidate its pharmacologically active compounds; mechanistic roles in animal models; and the impact of ash to moisture mix variation on potential hydrogen, microbial and antimicrobial activities in relation to shelf life, bioactivity and in vivo anti-oxidative roles for novel insights on preserving sample quality, safety, bioactivity and in-vivo anti-oxidative outcomes.